Method for preparing polysaccharide sodium hyaluronate composite gel by pre-crosslinking method

The preparation of polysaccharide sodium hyaluronate composite gel through two-step pre-crosslinking method solves the problem of low-molecular-weight glycosaminoglycans in the composite crosslinking gel with low effective crosslinking content, and achieves efficient improvement of the bioperformance and retention time of the gel.

CN119859286AActive Publication Date: 2025-04-22RUIJU BIOMEDICAL (SHENZHEN) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411989240.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-22
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In the prior art, low molecular weight glycosaminoglycans have a low effective crosslinking content in composite crosslinking gels, resulting in limited superposition of gel performance and inability to effectively improve biological performance and gel retention time.

Method used

The polysaccharide sodium hyaluronate composite gel was prepared by two-step pre-crosslinking method. First, the low-molecular polysaccharide was pre-crosslinked in the alkali solution to obtain a gel intermediate, and then secondary crosslinking with sodium hyaluronate was performed in the alkali solution to increase the effective crosslinking content of low-molecular-weight glycosaminoglycans.

Benefits of technology

Through this method, the effective cross-linking content of sulfated glycosaminoglycan in the composite gel is significantly improved, the bioperformance and retention time of the gel are improved, and the strength and biocompatibility of the gel are also significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223268930000041
    Figure BDA0005223268930000041
  • Figure BDA0005223268930000051
    Figure BDA0005223268930000051
  • Figure BDA0005223268930000052
    Figure BDA0005223268930000052
Patent Text Reader

Abstract

The invention relates to a method for preparing polysaccharide sodium hyaluronate composite gel by a pre-crosslinking method, and belongs to the technical field of high polymer material preparation. According to the method provided by the invention, the low-molecular polysaccharide is pre-crosslinked, then the sodium hyaluronate, the gel intermediate and the crosslinking agent are subjected to secondary crosslinking, and then the composite gel is prepared. The method provided by the invention is simple to operate, the low-molecular polysaccharide can be effectively cross-linked, the content of the low-molecular polysaccharide in the final product is increased, and the biological performance of the gel is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and particularly relates to a method for preparing a polysaccharide sodium hyaluronate composite gel by a pre-crosslinking method. Background Art

[0002] Hyaluronic acid (HA) is a linear, high-molecular-weight polysaccharide composed of glucuronic acid and glucosamine disaccharide units. It is present in many connective tissues, including the skin, vitreous humor, cartilage, and synovial fluid, where it plays physiological roles in moisturizing, nourishing, repairing, and preventing injuries. To date, a large number of HA products have been developed clinically, including ophthalmic viscoelastics and orthopedic viscosupplements, intra-articular injections for arthritis treatment, agents for preventing and treating postoperative adhesions, and facial fillers.

[0003] Low-molecular-weight glycosaminoglycans, such as chondroitin sulfate (CS), dermatan sulfate (DS), and heparin, are a class of biomaterials with exceptional properties. They are reported to reduce the viscosity of composite gels, thereby reducing injection pressure, offering significant advantages in the field of cosmetic fillers. Furthermore, sulfated glycosaminoglycans like chondroitin sulfate exhibit excellent antibacterial, anti-inflammatory, and wound-healing properties. Therefore, increasing the effective content of low-molecular-weight glycosaminoglycans is crucial for realizing the advantages of hyaluronic acid composite gels.

[0004] At present, there is less attention paid to the actual cross-linking content of low molecular weight glycosaminoglycans in composite cross-linked gels, especially sulfated glycosaminoglycans. Due to the problems of few active sites, large reaction steric hindrance, and low cross-linking efficiency caused by sulfate group occupancy, it is impossible to promote the formation of effective cross-linking and interpenetrating networks of low molecular weight glycosaminoglycans in composite gels, thereby hindering the superposition of the performance of composite gels after cross-linking. In the prior art, CS and HA are modified (methacrylation or aldehyde formation) so that the two can be spontaneously cross-linked. However, this pre-treatment operation is complicated, and the degree of modification and effect need to be further explored, which causes certain damage to the molecular weight of HA and CS. In WO2021137837A1, chondroitin sulfate and non-cross-linked hyaluronic acid are added to the cross-linked hyaluronic acid gel to promote extrusion, but the chondroitin sulfate in the gel obtained in this way is mostly in a free state and cannot exert its biological effect for a long time.

[0005] Another method involves a one-step process to prepare a composite cross-linked gel. Patent EP2011816B1 dissolves hyaluronic acid and chondroitin sulfate simultaneously in an alkaline solution and cross-links them using BDDE. However, because BDDE preferentially cross-links with hyaluronic acid, which has less steric hindrance and more cross-linking sites, in an alkaline environment, most of the chondroitin sulfate remains free and unlinked. This results in a low effective cross-linking content, hindering the bioperformance and gel retention time.

[0006] Therefore, a new method for preparing composite gels is needed to increase the content of low molecular weight glycosaminoglycans in the composite gels and the degree of effective cross-linking. Summary of the Invention

[0007] In view of the above technical background, the present invention provides a method for preparing a polysaccharide sodium hyaluronate composite gel, which is a new method suitable for industrial production. It is simple to operate and can effectively increase the effective cross-linking content of low molecular weight glycosaminoglycans in the cross-linked gel.

[0008] The present invention provides a method for preparing a polysaccharide sodium hyaluronate composite gel, which comprises the following steps:

[0009] 1) Pre-crosslinking: adding low molecular weight polysaccharide to an alkaline solution and adding a portion of a crosslinking agent to pre-crosslink the low molecular weight polysaccharide to obtain a gel intermediate;

[0010] 2) Secondary cross-linking: dissolving sodium hyaluronate in an alkaline solution, adding the gel intermediate and the remaining cross-linking agent to obtain a mixture, and performing secondary cross-linking to obtain a composite gel;

[0011] The low molecular weight polysaccharide is selected from one or more of chondroitin sulfate (CS), dermatan sulfate (DS), heparan sulfate (HS), keratan sulfate (KS), heparin, sulfated sodium hyaluronate and other sulfated glycosaminoglycans.

[0012] In some embodiments, the low molecular weight polysaccharide is preferably one or more of chondroitin sulfate, dermatan sulfate, and sulfated sodium hyaluronate.

[0013] The cross-linking agent is selected from any one of 1,4-butanediol diglycidyl ether (BDDE), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane and 1,2-ethylene glycol diglycidyl ether; preferably BDDE.

[0014] Furthermore, the alkaline solution is an aqueous sodium hydroxide solution.

[0015] Furthermore, the mass concentration of the sodium hydroxide aqueous solution is 0.5wt% to 3wt%, preferably 0.5wt% to 2wt%.

[0016] Furthermore, the molecular weight of the low molecular weight polysaccharide is 1×10 4 Da~5×10 5 Da, preferably 1×10 4 Da~1×10 5 Da, more preferably 1×10 4 Da~8×10 4 Da.

[0017] Furthermore, the molecular weight of the sodium hyaluronate is in the range of 1×10 6 Da~3×10 6 Da, preferably 2×10 6 Da~3×10 6 Da.

[0018] Furthermore, in the step 1) of pre-crosslinking, the ratio of the volume (mL) of the alkaline solution to the mass (g) of the low molecular weight polysaccharide is 1 mL: (0.1-0.8) g, preferably 1 mL: (0.2-0.6) g.

[0019] Furthermore, the mass ratio of the cross-linking agent to the sum of sodium hyaluronate and low molecular weight polysaccharide is (0.05-0.2):1, preferably (0.08-0.15):1. The molar amount of the partial cross-linking agent added in step 1) pre-cross-linking accounts for 50% to 100% of the total molar amount of the cross-linking agent, preferably 55% to 100% of the total molar amount of the cross-linking agent.

[0020] Furthermore, the pre-crosslinking time is 1 h to 9 h, preferably 2 h to 7 h.

[0021] Furthermore, the pre-crosslinking temperature is 30°C to 60°C, preferably 40°C to 60°C.

[0022] Furthermore, the concentration (mass / volume, w / v) of the sodium hyaluronate in the alkaline solution is 10% to 25%, preferably 14% to 20%.

[0023] Furthermore, the mass ratio of the sodium hyaluronate to the low molecular weight polysaccharide is (1-10):1, preferably (1.5-5):1.

[0024] According to the present invention, the secondary crosslinking can be achieved by the following method: the mixture is first reacted at temperature A, and then crosslinked at temperature B to prepare a composite gel; or the mixture is reacted at a temperature of 40°C to 50°C to obtain a composite gel.

[0025] Furthermore, the temperature A may be 0°C to 20°C, preferably 5°C to 12°C.

[0026] Furthermore, the mixture is reacted at the temperature A for 24 hours to 72 hours, preferably 36 hours to 60 hours.

[0027] Furthermore, the temperature B is 30°C to 60°C, preferably 40°C to 60°C, and more preferably 50°C.

[0028] Furthermore, the mixture is reacted at the temperature B for 2 h to 10 h, preferably 3 h to 5 h.

[0029] In some embodiments, the preparation method further comprises: dialyzing the gel obtained after the secondary cross-linking in PBS buffer. In some embodiments, the preparation method further comprises: soaking the gel obtained after the secondary cross-linking in PBS buffer.

[0030] In certain embodiments, the preparation method further includes: cutting the gel obtained after the secondary cross-linking into small pieces, soaking them in PBS buffer solution, replacing the PBS buffer solution, and fully soaking to remove unreacted cross-linking agent; then sieving the gel through a 160-mesh sieve to form small gel particles, and then mechanically homogenizing to prepare a polysaccharide sodium hyaluronate composite gel.

[0031] In certain embodiments, the preparation method further includes: cutting the gel obtained after the secondary cross-linking into small pieces, soaking them in a PBS buffer solution containing hydrochloric acid, replacing the PBS buffer solution, and fully soaking to remove unreacted cross-linking agent; then sieving the gel through a 160-mesh sieve to form small gel particles, and then mechanically homogenizing to prepare a polysaccharide sodium hyaluronate composite gel.

[0032] In order to obtain a sterile gel or a gel that meets the quality requirements for injection, the composite gel can be sterilized, such as terminal sterilization, moist heat sterilization, or irradiation sterilization, or can be prepared under aseptic conditions using sterile raw materials to obtain an injectable composite gel.

[0033] The PBS buffer solution can be prepared by one or more of sodium chloride, potassium chloride, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate and water. In some embodiments, the PBS buffer solution is prepared by sodium chloride, disodium hydrogen phosphate, sodium dihydrogen phosphate and water. In some embodiments, the PBS buffer solution is prepared by sodium chloride, disodium hydrogen phosphate, potassium dihydrogen phosphate and water.

[0034] The pH of the PBS buffer solution may be 6.5 to 7.5. In certain embodiments, the pH of the PBS buffer solution is 6.5 to 6.8. In certain embodiments, the pH of the PBS buffer solution is 6.8 to 7.4.

[0035] The second aspect of the present invention provides a role of the polysaccharide sodium hyaluronate composite gel in preparing medical cosmetic injections for separating, replacing or filling biological tissues, or increasing the volume of biological tissues, or for filling wrinkles, concealing scars, or increasing the volume of lips.

[0036] The advantages of the preparation method provided by the present invention are mainly:

[0037] 1. The present invention uses a two-step pre-crosslinking process to prepare composite gels, which can increase the effective crosslinking content of sulfated glycosaminoglycans in the gel. Due to its configuration and the steric hindrance of sulfate groups, BDDE typically preferentially crosslinks with HA, resulting in a low crosslinking content of sulfated glycosaminoglycans in the gel, with most existing in a free state. Existing preparation methods cannot avoid the difficulty of crosslinking sulfated glycosaminoglycans in composite gels. The present invention solves this problem by first preparing a polysaccharide cross-linked gel intermediate and then mixing it with an HA solution for secondary crosslinking. This process ensures effective chemical crosslinking of sulfated glycosaminoglycans, improves bidirectional crosslinking with HA chains, forms an interpenetrating crosslinked network, and thereby increases the content of sulfated glycosaminoglycans in the final product. Compared to other methods, this solution can increase the percentage of crosslinked sulfated glycosaminoglycans in the gel to 20% to 85%, an increase of 2 to 12 times compared to other existing technical solutions. While the proportion of effectively cross-linked sulfated glycosaminoglycans is increased, the strength of the gel is also significantly improved compared to the one-step method.

[0038] 2. The present invention uses a two-step pre-crosslinking method to prepare composite gels. Compared with the one-step method, more controllable factors can be adjusted, allowing for customized gels. This method is also applicable to the preparation of composite cross-linked samples of various sulfated glycosaminoglycans and modified polysaccharides. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the invention. The experimental methods in the following examples where specific conditions are not specified are generally performed under conventional conditions.

[0040] Unless otherwise specified, the raw materials and reagents used in the examples are commercially available.

[0041] The room temperature described in the examples is 20°C to 30°C.

[0042] Unless otherwise specified, the reagents were used directly without purification. All reagents were purchased from commercial suppliers, such as Aldrich, and used without further treatment.

[0043] In the following examples / comparative examples, the PBS buffer solution was prepared from sodium chloride, disodium hydrogen phosphate, sodium dihydrogen phosphate and water, with a concentration of 0.01 mol / L and a pH of 6.8.

[0044] Example 1: Effect of crosslinking time on gel properties

[0045] Dissolve 2.80 g of CS (molecular weight 46,000 Da) in 5.6 mL of 1 wt% NaOH. After the CS is completely dissolved, add 0.8350 g of BDDE, using a crosslinker dosage of 17.4% for a total crosslinking degree. Continue stirring for 0.5 h. Crosslink the CS solution at 50°C for a period of time (pre-crosslinking).

[0046] 4.80 g of HA (molecular weight 2.3 million Da) powder was slowly added to 24.4 mL of 1 wt% NaOH solution and stirred to dissolve uniformly to obtain HA solution;

[0047] The CS cross-linking solution obtained after pre-cross-linking was slowly added to the HA solution, with rapid stirring to fully blend the two (total HA concentration of 16%, w / v). Stirring was continued for 30 minutes. The HA / CS mixture was allowed to cross-link at 10°C for 48 hours, then heated to 50°C for a further period of cross-linking (secondary cross-linking). The cross-linked gel was dialyzed against PBS buffer for 36 hours, with three changes of PBS buffer. The dialyzed sample was homogenized using a 160-mesh sieve to obtain a composite gel.

[0048] The composite gel obtained under each condition was partially degraded and tested. 1 H NMR was used to calculate the cross-linking degree R (R = BDDE mole number / (total HA / CS disaccharide unit mole number)) based on the characteristic peaks of BDDE and HA / CS disaccharide units. A portion of the gel was taken to detect the total HA content, free HA content, total CS content, and free CS content, and the effective HA cross-linking ratio and CS effective cross-linking ratio were calculated, respectively, using the formula (1-free content / total content)*100%. A portion of the gel was placed on a rotational rheometer in flat plate mode with a fixed strain of 0.01%. A frequency sweep (0.01 Hz to 100 Hz) was selected to test the viscoelasticity of the gel at 0.1 Hz.

[0049] The relevant specific parameters and experimental results of each experiment in Example 1 are shown in Table 1.

[0050] Table 1: Process conditions and gel test results of each experiment in Example 1

[0051]

[0052] Example 2: Effect of BDDE Addition Method on Gel Properties

[0053] 2.80 g of CS (molecular weight 46,000 Da) was dissolved in 5.6 mL of 1 wt% NaOH to obtain a CS solution. BDDE (0.6670 g, 0.5000 g, and 0.3840 g) was added to the CS solution according to the crosslinking agent dosage of 40%, 30%, and 23% pre-crosslinking degrees, respectively, and crosslinked at 50°C for 3 h.

[0054] 4.8 g of HA (molecular weight 2.3 million Da) was dissolved in 24.4 mL of 1 wt% NaOH to obtain a HA solution;

[0055] The CS cross-linking solution was then mixed evenly with the HA solution (total HA concentration was 16%, w / v). The total amount of BDDE (0.6670 g) was calculated as the cross-linking agent for a total cross-linking degree of 13.9%. The remaining BDDE was added to the HA / CS mixed solution and stirred for 10 minutes. The HA / CS mixture was allowed to cross-link at 10°C for 48 hours, then heated to 50°C and cross-linked for another 3 hours. The cross-linked gel was dialyzed in PBS buffer for 36 hours, during which time the PBS buffer was changed three times to remove residual small molecules and impurities. The dialyzed sample was homogenized using a 160-mesh sieve to obtain a composite gel.

[0056] The same method as in Example 1 was used to test various properties. The relevant specific parameters and experimental results of each experiment in Example 2 are shown in Table 2.

[0057] Table 2: Process conditions and gel test results of each experiment in Example 2

[0058]

[0059] Based on the difference between the results of Experiment 2-1 and the results of Experiments 2-2 and 2-3, it can be determined that under the condition of the same total cross-linking degree, adding BDDE in two steps can improve the effective cross-linking ratio and gel strength of HA compared to adding BDDE all at once.

[0060] Example 3: Effect of HA concentration on gel properties

[0061] 2.80 g of CS (molecular weight 46,000 Da) was dissolved in 5.6 mL of 1 wt% NaOH to obtain a CS solution. BDDE (0.3840 g) was added to the CS solution according to the amount of crosslinker used to achieve a pre-crosslinking degree of 23%, and the CS solution was crosslinked at 50°C for 3 h.

[0062] 4.80 g of HA (molecular weight 2.3 million Da) was dissolved in 21.1 mL and 18.4 mL of 1 wt% NaOH, respectively, to obtain HA solutions;

[0063] The CS cross-linking solution was then mixed evenly with the HA solution (total HA concentrations were 18% and 20%, w / v, respectively). The total amount of BDDE (0.6670 g) was calculated as the cross-linking agent for a total cross-linking degree of 13.9%. The remaining BDDE was added to the HA / CS mixed solution and stirred for 10 minutes. The HA / CS mixture was allowed to cross-link at 10°C for 48 hours, then heated to 50°C and cross-linked for another 3 hours. The cross-linked gel was dialyzed in PBS buffer for 36 hours, during which time the PBS buffer was replaced three times to remove residual small molecules and impurities. The dialyzed sample was homogenized using a 160-mesh sieve to obtain a composite gel.

[0064] The same method as in Example 1 was used to test various properties. The relevant specific parameters and experimental results of each experiment in Example 3 are shown in Table 3.

[0065] Table 3: Process conditions and gel test results of each experiment in Example 3

[0066]

[0067] According to the results of experiments 2-3 and 3-1, as the HA concentration increases, the HA chains become more tightly entangled, the gel strength increases, and the effective cross-linking ratio of HA increases; in addition, the HA chains can also form a denser double network structure with CS, effectively increasing the effective cross-linking ratio of CS; according to the results of experiments 3-1 and 3-2, when the HA concentration is too high, the solution hardness is high, which is not conducive to the mixing of CS and HA raw materials, and the effective cross-linking content ratio of CS is slightly reduced.

[0068] Example 4

[0069] Dissolve 2.80 g of CS (molecular weight 46,000 Da) and 2.80 g of DS (molecular weight 35,000 Da) in 4.7 mL of 1 wt% NaOH. Once the raw materials are completely dissolved, add 0.8350 g of BDDE and continue stirring for 0.5 h. Crosslink the raw material solution at 50°C for 3 h.

[0070] 4.80 g of HA (molecular weight 2.3 million Da) powder was slowly added to 25.3 mL of 1 wt% NaOH solution and stirred to dissolve uniformly to obtain HA solution;

[0071] The pre-crosslinked low-molecular-weight polysaccharide gel intermediate was slowly added to the HA solution with rapid stirring to fully blend the two (total HA concentration was 16%, w / v). Stirring was then continued for 30 minutes. The HA / CS mixture was heated to 50°C and crosslinked for another 3 hours. The cross-linked gel was dialyzed against PBS buffer for 36 hours, changing the PBS buffer three times. The dialyzed sample was homogenized using a 160-mesh sieve to obtain a composite gel.

[0072] The same method as in Example 1 was used to test various properties. The relevant specific parameters and experimental results of each experiment in Example 4 are shown in Table 4.

[0073] Table 4: Process conditions and gel test results of each experiment in Example 4

[0074]

[0075] Example 5

[0076] 2.80 g of CS (molecular weight 46,000 Da) was dissolved in 5.6 mL of 1 wt% NaOH to obtain a CS solution. BDDE (0.3840 g) was added to the CS solution at a pre-crosslinking degree of 23%, and the CS solution was crosslinked at 50°C for 3 h.

[0077] 4.80 g of HA (molecular weight 2.3 million Da and 1.5 million Da) were dissolved in 21.1 mL of 1 wt% NaOH to obtain HA solutions;

[0078] The CS cross-linking solution was then mixed evenly with the HA solution (total HA concentration was 18%, w / v). The total amount of BDDE was calculated as 0.6670 g, with a total cross-linking degree of 13.9%. The remaining BDDE was added to the HA / CS mixed solution and stirred for 10 minutes. The mixed solution was allowed to stand at 10°C for cross-linking for 48 hours, then heated to 50°C and continued cross-linking for 3 hours. The cross-linked gel was placed in PBS buffer and soaked for 40 hours, during which the PBS buffer was changed 4 times to remove residual small molecules and impurities. After soaking, the sample was homogenized using a 160-mesh sieve to obtain a composite gel.

[0079] The same method as in Example 1 was used to test various properties. The relevant specific parameters and experimental results of each experiment in Example 5 are shown in Table 5.

[0080] Table 5: Process conditions and gel test results of each experiment in Example 5

[0081]

[0082] According to the results of Experiments 3-1 and 5-1, compared with dialysis purification, immersion purification can remove most of the free raw materials and increase the effective cross-linking ratio of HA and CS in the final product. According to the results of Experiments 3-1 and 5-2, as the molecular weight of HA decreases, the gel strength decreases by about 39%. Since the low molecular weight raw materials have better solubility and the degree of cross-linking increases, the effective cross-linking ratio of HA and CS increases.

[0083] Comparative Example 1 One-step method

[0084] 4.80g of sodium hyaluronate (molecular weight 2.3 million Da) powder was added to 26.7mL of 1wt% NaOH solution. After the sodium hyaluronate was evenly dissolved, 2.80g of CS (molecular weight 46,000 Da) was slowly added and stirred until it became light yellow and transparent. 0.6670g of BDDE was added and stirred for 30 minutes. The mixture was reacted at 10°C for 48 hours and then at 50°C for 3 hours. The cross-linked gel was dialyzed in PBS buffer for 36 hours, during which the PBS buffer was changed three times to remove residual small molecules and impurities. The dialyzed sample was homogenized using a 160-mesh sieve.

[0085] The same method as in Example 1 was used to test various properties; the experimental parameters and test results are shown in Table 6.

[0086] Comparative Example 2CS was added as free

[0087] Add 4.80 g of sodium hyaluronate (molecular weight 2.3 million Da) powder to 26.7 mL of 1 wt% NaOH solution and stir to dissolve evenly. Add 0.6670 g of BDDE and stir for 30 minutes. First, react at 10°C for 48 hours, then at 50°C for 3 hours. The cross-linked gel is dialyzed against PBS buffer to remove residual small molecules and impurities. After dialysis, the sample is homogenized using a 160-mesh sieve to obtain HA gel.

[0088] Dissolve CS (molecular weight 46,000 Da) in PBS buffer to prepare a 2 wt% CS solution. Add an appropriate amount of homogenized HA gel to the 2 wt% CS solution and stir for 30 minutes. Maintain a HA to CS mass ratio of 1.7:1 and a combined HA and CS concentration of 20 mg / mL to 30 mg / mL.

[0089] The same method as in Example 1 was used to test various properties; the experimental parameters and test results are shown in Table 6.

[0090] Comparative Example 3: HA pre-crosslinking, secondary crosslinking after CS addition

[0091] Add 4.80g of sodium hyaluronate (molecular weight 2.3 million Da) powder to 21.1mL of 1wt% NaOH solution and stir to dissolve thoroughly. Weigh 0.3840g of BDDE (a crosslinker dosage of 23% for pre-crosslinking) and add it to the HA solution. Mix thoroughly, and crosslink the mixture at 50°C for 3 hours. Weigh 2.80g of CS (molecular weight 46,000 Da) and dissolve thoroughly in 5.6mL of 1wt% NaOH solution. Add this to the HA crosslink solution and stir to mix thoroughly. Add 0.6670g of BDDE (a crosslinker dosage of 13.9% for a total crosslinking degree) to the HA / CS mixture and stir for 10 minutes. Allow the mixture to crosslink at 10°C for 48 hours, then raise the temperature to 50°C and continue crosslinking for 3 hours. The crosslinked gel was dialyzed against PBS buffer for 36 hours, changing the PBS buffer three times to remove residual small molecules and impurities. After dialysis, the sample was homogenized using a 160-mesh sieve.

[0092] The same method as in Example 1 was used to test various properties; the experimental parameters and test results are shown in Table 6.

[0093] Table 6: Process conditions and gel test results of each comparative example

[0094]

[0095] The experimental results show that compared with the two-step pre-crosslinking method provided by the present invention, the effective crosslinking ratio of CS in the comparative examples is relatively low. The gels prepared by the pre-crosslinking methods in Experiments 3-1 and 5-1 showed significant improvements in both the effective crosslinking ratio of CS and strength compared to the gels prepared in Comparative Examples 1 and 2. Compared with Comparative Example 3, the strengths of the two gels were similar, but the effective crosslinking ratio of CS increased by nearly 30% and 60%, respectively. The gels obtained by the methods provided by the present invention help improve the biocompatibility of the composite gels and demonstrate the excellent antibacterial and anti-inflammatory effects of low-molecular-weight polysaccharides, such as promoting wound healing and prolonging the efficacy period.

[0096] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other manner. Any person skilled in the art may utilize the above-disclosed technical content to modify or modify the present invention into equivalent embodiments. However, any simple modifications, equivalent variations, and modifications to the above embodiments that do not depart from the technical content of the present invention and are based on the technical essence of the present invention remain within the scope of protection of the present invention.

Claims

1. A method for preparing a polysaccharide sodium hyaluronate composite gel, characterized in that: The following steps are involved: 1) Pre-crosslinking: adding low molecular weight polysaccharide to an alkaline solution, adding part of the crosslinking agent, pre-crosslinking the low molecular weight polysaccharide to obtain a gel intermediate; 2) Secondary cross-linking: dissolving sodium hyaluronate in an alkaline solution, adding the gel intermediate and the remaining cross-linking agent to obtain a mixture, and performing secondary cross-linking to obtain a composite gel; Wherein, the low molecular weight polysaccharide is selected from one or more of chondroitin sulfate, dermatan sulfate, heparan sulfate, keratan sulfate, heparin, and sulfated sodium hyaluronate.

2. The preparation method according to claim 1, characterized in that: The low molecular weight polysaccharide is one or more of chondroitin sulfate, dermatan sulfate, and sulfated sodium hyaluronate; and / or The crosslinking agent is selected from any one of 1,4-butanediol diglycidyl ether, 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane and 1,2-ethylene glycol diglycidyl ether; preferably 1,4-butanediol diglycidyl ether.

3. The preparation method according to claim 1, characterized in that: The alkaline solution is a sodium hydroxide aqueous solution, and the mass concentration of the sodium hydroxide aqueous solution is 0.5wt% to 3wt%, preferably 0.5wt% to 2wt%.

4. The preparation method according to claim 1, characterized in that: The pre-crosslinking temperature is 30°C to 60°C, preferably 40°C to 60°C, and more preferably 50°C.

5. The preparation method according to claim 1, characterized in that: The pre-crosslinking time is 1 h to 9 h, preferably 2 h to 7 h.

6. The preparation method according to claim 1, characterized in that: It includes at least one of the following conditions: The molecular weight range of the low molecular weight polysaccharide is 1×10 4 Da~5×10 5 Da; The molecular weight range of the sodium hyaluronate is 1×10 6 Da~3×10 6 Da; In step 1), the ratio of the volume of the alkaline solution to the mass of the low molecular weight polysaccharide in the pre-crosslinking is 1 mL: (0.1-0.8) g; The molar amount of the crosslinking agent added in step 1) pre-crosslinking accounts for 50% to 100% of the total molar amount of the crosslinking agent; In step 2), the concentration of the sodium hyaluronate after being dissolved in the alkaline solution is 10% to 25%; The mass ratio of the cross-linking agent to the sum of hyaluronic acid and low molecular weight polysaccharide is (0.05-0.2):1; and The mass ratio of the sodium hyaluronate to the low molecular weight polysaccharide is (1-10):

1.

7. The preparation method according to claim 1, characterized in that: It includes at least one of the following conditions: The molecular weight of the low molecular weight polysaccharide is 1×10 4 Da~1×10 5 Da; The molecular weight range of the sodium hyaluronate is 2×10 6 Da~3×10 6 Da; In step 1), the ratio of the volume of the alkaline solution to the mass of the low molecular weight polysaccharide in the pre-crosslinking is 1 mL: (0.2-0.6) g; The molar amount of the crosslinking agent added in step 1) pre-crosslinking accounts for 55% to 100% of the total molar amount of the crosslinking agent; In step 2), the concentration of the sodium hyaluronate after being dissolved in the alkaline solution is 14% to 20%; The mass ratio of the cross-linking agent to the total of sodium hyaluronate and low molecular weight polysaccharides is (0.08-0.15):1; and The mass ratio of the sodium hyaluronate to the low molecular weight polysaccharide is (1.5-5):

1.

8. The preparation method according to claim 1, characterized in that: The secondary crosslinking comprises: The mixture is first reacted at temperature A and then at temperature B to obtain a composite gel; or The mixture reacts at a temperature of 40°C to 50°C to obtain a composite gel.

9. The preparation method according to claim 8, characterized in that: The secondary crosslinking includes at least one of the following conditions: The temperature A is 0°C to 20°C, preferably 5°C to 12°C; The mixture is reacted at the temperature A for 24 h to 72 h, preferably 36 h to 60 h; The temperature B is 30°C to 60°C, preferably 40°C to 60°C, and more preferably 50°C; and The mixture is reacted at the temperature B for 2 h to 10 h, preferably 3 h to 5 h.

10. The preparation method according to claim 8, characterized in that: The preparation method further comprises: dialyzing the gel obtained after the secondary cross-linking in a PBS buffer solution, or soaking the gel obtained after the secondary cross-linking in a PBS buffer solution.

Citation Information

Patent Citations

  • Co-reticulated polysaccharide gel

    EP2011816B1

  • A novel viscoelastic formulation for osteoarthritis treatment and a production method thereof

    WO2021137837A1

  • Preparation method and application of injectable sodium hyaluronate-heparin precursor composite gel

    CN118252981A

  • Preparation method of polysaccharide sodium hyaluronate composite gel

    CN118546395A

  • Preparation method and preparation device of cross-linked sodium hyaluronate gel for injection

    CN118978721A